Kinetic monte carlo simulations of solid oxide fuel cell - Rojana Pornprasertsuk (2018)
The kinetic Monte Carlo technique was employed to simulate an entire solid oxide fuel cell (SOFC) during operation to gain insight into the electrode kinetics and rate-limiting steps in the intermediate temperature range. By combining the quantum simulation studies of oxide ion migration in the fuel cell electrolyte with the experimental studies of the cathode and anode reaction rates, a complete SOFC can be modeled. To study the effect of triple phase boundaries and the size of the catalyst, simulations were performed for different sizes of Pt clusters on the electrolyte surface. The results confirm that the charge-transfer reaction rates depend on the catalyst size. The fuel cell with smaller catalyst particles produces higher power density as expected. The reaction rates of each process were recorded as a function of time. The overpotentials were subsequently determined as a function of catalyst size. The results show that oxygen adsorption is the slowest step on the cathode, while water formation is the slowest step on the anode. The methodology can be used to optimize the catalyst size on both electrodes to reduce the activation loss in intermediate temperature SOFCs. © 2009 The Electrochemical Society.